Schlaf der Vernunft. - Gassner, Hubertus; Brüderlin, Markus; Loers, Veit; Burckhardt, Lucius (Kassel : Museum Fridericianum, 1988)
Aguirre, Javier ; Armleder, John M; ; Asdrubali, Gianni ; Barry, Robert ; Blum, Heiner ; Colombo, Gianni ; Deacon, Richard ; Domela, Cesar ; Ettl, Georg ; Förg, Günter ; Fruhtrunk, Günter ; Judd, Donald ; Koons, Jeff ; Lichtenstein, Roy ; Merkel, Klaus ; Mosset, Olivier ; Nauman, Bruce ; Renouf, Edda ; Rockenschaub, Gerwald ; Saffaro, Lucio ; Schütte, Thomas ; Staccioli, Mauro ; Steinbach, Haim ; Welling, James
Schlaf der Vernunft, Museum Fridericianum, Kassel, 21. Februar - 23. Mai 1988
boek